Quality Of Service (QOS) Pengujian Functional Suitability Berdasarkan ISO 25010 Sistem Inventaris Berbasis Web - Rahmadi Asri; Laila Wati; Ratna Dewi; Amna Amna (Pixel :Jurnal Ilmiah Komputer Grafis, 2022)
Inventory Information System is an information technology-based system that aims to assist organizations or institutions in managing and monitoring inventory more efficiently and provides an overview of the inventory information system, the main focus of its development, and the expected benefits of implementing this system. Using a manual system for each product written with a book, of course, is not efficient can result in inventory data easily lost and damaged, easy to occur errors or data loss. To overcome the occurrence of these problems is there is a web-based inventory information system application to solve the occurrence of errors that are often found in the world of work. Based on the results obtained This research can overcome the problem of data loss, data errors, with the help of this information system can help solve problems that often occur. This information system is made according to the needs of the White Elephant University efficiently and accurately.